2019
DOI: 10.3390/medicina55070377
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus and Infertility

Abstract: Background and objectives. Human papillomavirus (HPV) is the most commonly sexually transmitted infection. Recent evidence suggests that an HPV infection may affect fertility. The aim of the study was to determine the prevalence of HPV infections among couples undergoing in vitro fertilization (IVF) and to identify their awareness of HPV. Material and Methods. A total of 200 samples were collected from couples who received IVF treatment during 2017–2018 in Vilnius University Hospital Santaros Klinikos (VUH SK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 18 publications
4
22
0
3
Order By: Relevance
“…This distribution of HPV genotypes contrasts with the report that HPV16 was the most represented in women without C. trachomatis coinfection (Seraceni et al, 2016), but in agreement with the recent Italian data that described these genotypes as the most frequent types associated with coinfections (Carozzi et al, 2014) in which HPV 52, 51, and 39 of groups 1, 2 A or 2 B have been classified as cervical carcinogens (Clarke et al, 2018). More interestingly, HPV 52 was also the genotype that is most frequently detected among women from ART, which reinforced the notion that HPV 52 was most commonly found in couples undergoing in vitro fertilization treatment, and in the case of low sperm concentration and reduced sperm motility, as recently presented from a Lithuanian report (Jersoviene et al, 2019).…”
Section: Discussionsupporting
confidence: 52%
“…This distribution of HPV genotypes contrasts with the report that HPV16 was the most represented in women without C. trachomatis coinfection (Seraceni et al, 2016), but in agreement with the recent Italian data that described these genotypes as the most frequent types associated with coinfections (Carozzi et al, 2014) in which HPV 52, 51, and 39 of groups 1, 2 A or 2 B have been classified as cervical carcinogens (Clarke et al, 2018). More interestingly, HPV 52 was also the genotype that is most frequently detected among women from ART, which reinforced the notion that HPV 52 was most commonly found in couples undergoing in vitro fertilization treatment, and in the case of low sperm concentration and reduced sperm motility, as recently presented from a Lithuanian report (Jersoviene et al, 2019).…”
Section: Discussionsupporting
confidence: 52%
“…The data support the presence of HPV in semen and its proposed role in decreased fertility (20,21). Other studies indicated that HPV infection of semen represents a risk factor for male fertility abnormality (1,3). A study found the most common HPV genotype among couples undergoing IVF treatment was 52 (1).…”
Section: Discussionsupporting
confidence: 79%
“…HPV is the most prevalent sexually transmitted infection among men and women of reproductive age worldwide (1), and its effect on cancer induction is well known (2). HPV infections are significantly associated with many alterations of reproductive function (1).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in SARS-CoV, which also targeted the same receptor, have revealed that numerous patients had evidence of testicular inflammation (orchitis) [ 230 ]. Indeed, a range of other viral infections such as HIV, mumps, hepatitis B, and human papillomavirus has been shown to cause male sterility, altered expression of hormones, and may even be linked to increased risk of testicular cancer [ 231 , 232 , 233 , 234 , 235 ]. One study demonstrated that the ratio of testosterone and follicle-stimulating hormone to serum luteinizing hormone was significantly decreased in young adult male COVID-19 patients ( n = 81) compared to controls ( n = 100) [ 229 ].…”
Section: How Might Ergothioneine Be Beneficial In Alleviating Covimentioning
confidence: 99%